DESENVOLVIMENTO E APLICAÇÃO DE METODOLOGIA ANALÍTICA (CLAE/FL) PARA DETERMINAÇÃO DE FLUOROQUINOLONAS EM SEDIMENTO ESTUARINO DA ILHA DO MARANHÃO - Neves, Mônica Araujo das (2014)
Drugs in the planet have increased during last decades. Such compounds can cause adverse impact on ecosystems. Soon, more effective analytical methods are essential for the study of new pollutants, especially in magazines whose headquarters are very complex as mangrove sediments. Therefore, this study aimed to improve an analytical method to assess the occurrence of fluoroquinolone antibiotics, ciprofloxacin (CIP), levofloxacin (LEV) and norfloxacin (NOR), in sediment samples from the Paciência river located on the Maranhão island using the technique of ultrasound-assisted extraction, extraction phase solid and liquid chromatography (HPLC/FD). According to the study, the method was linear (r²> 0.99), recovery ranging from 73.73 to 88.85%, precise (RSD <20%), selective and sensitive (detection limit for CIP, LEV and NOR 9.32; 17.78 and 4.42 µg.kgˉ¹, respectively, and limit of quantitation of 20 µg.kgˉ¹ for all three drugs) for quantification of fluoroquinolones in estuarine sediments. Other relevant aspects of the method developed in this work were the simplicity, low cost and absence of interfering to a very complex environmental matrix as are the mangrove sediments. When evaluating the sediment at various points of the river there was contamination at three points by CIP ranging from 56.55 to 70.45 µg.kgˉ¹ These results are similar to those found around the planet to polluted regions and they are of concern due to the effects of these antibiotics in the ecosystem.